The Assessment of Visuospatial Skills and Verbal Fluency in the Diagnosis of Alzheimer’s Disease - Dalida Borbala Berente; Dalida Borbala Berente; Anita Kamondi; Anita Kamondi; Andras Attila Horvath; Andras Attila Horvath (Frontiers in Aging Neuroscience, 2022)
BackgroundIn the diagnosis of Alzheimer’s disease (AD), examining memory is predominant. Our aim was to analyze the potential role of various cognitive domains in the cognitive evaluation of AD.MethodsIn total, 110 individuals with clinically defined AD and 45 healthy control participants underwent neuropsychological evaluation including Addenbrooke’s Cognitive Examination (ACE). Patients with AD were selected in three groups based on disease duration in years (Group 1: ≤2 years, n = 36; Group 2: 2–4 years, n = 44; Group 3: ≥4 years, n = 30). Covariance-weighted intergroup comparison was performed on the global cognitive score and subscores of cognitive domains. Spearman’s rho was applied to study the correlation between cognitive subscores and disease duration. The Wilcoxon signed-rank test was used for within-group analysis among ACE cognitive subscores.ResultsSignificant difference was found between ACE total scores among groups (χ2 = 119.1; p < 0.001) with a high negative correlation (p < 0.001; r = −0.643). With a longer disease duration, all the subscores of ACE significantly decreased (p-values < 0.001). The visuospatial score showed the strongest negative correlation with disease duration with a linear trajectory in decline (r = −0.85). In the early phase of cognitive decline, verbal fluency was the most impaired cognitive subdomain (normalized value = 0.64), and it was significantly reduced compared to all other subdomains (p-values < 0.05).ConclusionWe found that the impairment of verbal fluency is the most characteristic feature of early cognitive decline; therefore, it might have crucial importance in the early detection of AD. Based on our results, the visuospatial assessment might be an ideal marker to monitor the progression of cognitive decline in AD.